A sleeping dragon - Rushby, Pamela; Pelham-Thorman, Carol (Macmillan Education Australia South Yarra, Vic., 1997)
A Sleeping Dragon is a thrilling fantasy novel by Joel Rosenberg, where a group of college students is transported into a magical world that mirrors a role-playing game they once played. As they navigate this dangerous new reality, they must take on the roles of their game characters and face mystical creatures, including a slumbering dragon, in order to survive. The story explores themes of adventure, friendship, and personal growth, as the characters grapple with their new identities and the challenges of a world filled with magic and peril. It$1 (Bs an exciting blend of fantasy and action, perfect for fans of role-playing games and adventure stories.s